Study on function and appearance design of smart street lamps based on Kansei engineering: a literature review - Junchao, Ge; Tze Fong, Go; Hiu Hong, Teo; Lipeng, Wang (Penerbit Universiti Kebangsaan Malaysia, 2023)
The potential of smart cities to alleviate the challenges of urban development in relation to population, resources, and environment is widely recognized, making it a key urban development trend for the future. Smart street lamps (SSLs) are a crucial component of smart city infrastructure. However, their current unreasonable function settings and appearance design do not meet the emotional needs of residents and come at a high construction cost, resulting in decreased user satisfaction. Based on WOS and CNKI databases, 39 literatures on the aspects of theory, steps and technologies of KE, 32 literatures on the development, basic functions, construction, existing problems, and key technologies of SSLs, and 6 papers on street lamps functions or appearance design research based on KE be reviewed in this paper. Therefore, the application of KE method in SSL design be extensively reviewed, with emphasis on the future development direction of KE, the design principles of SSLs, and the implementation of KE in SSL design. This review aims to summarize the research gaps, future research directions, and future development trends of KE and SSL. Ultimately, the review concludes that the integration of KE in SSL design research is crucial to improve SSL products’ rationality, openness, and amicability, guided by scienti ic SSL design principles.